Pengaruh Keterampilan Kerja, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Dinas Pemberdayaan Masyarakat dan Desa (DPMD) Kota Sungai Penuh - Dona Elvia Desi; Melifia Liantifa (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to determine the Effect of Work Skills, Work Discipline and Work Environment on the Performance of Employees of the Community and Village Empowerment Service of Sungai Penuh City, totaling 23 respondents. Data collection in this study is primary data collected through distributing questionnaires to respondents. This research method uses qualitative methods, while the analytical tools used are multiple linear regression, t test, f test, and coefficient of determination test. he results showed that partially there was an influence between work skills (X1) on employee performance (Y) as evidenced by the value of t arithmetic t table (2,239 ˃ 2,09302) with a significant value = 0,037 < 0,050. Where the magnitude of the influence of work skills on employee performance is 8,5%. There is a positive and significant influence between work discipline (X2) partially on employee performance (Y) it is proved by t arithmetic ˃ t table (2,729 ˃ 2,09302) or Sig = 0,013 < 0,050. Where the magnitude of the influence of work discipline on employee performance is 11,2%. There is an influence between the non-physical work environment (X3) on employee performance (Y) it is proved by t arithmetic ˃ t table (4,213 ˃ 2,09302) or sig = 0,000 < 0,050. Where the magnitude of the influence of the non-physical work environment on employee performance is 33,2 %. There is a simultaneous influence between work skills, work discipline and work environment on employee performance at the office of community empowerment and village in sungai penuh city is 53,0% while the rest (100-53,0%), which is equal to 47% explained by other causal factors not examined in this study.